Do homegardens act as agent of agrobiodiversity conservation: a case study of homegardens of diverse socio-ecological zones in the Brahmaputra Valley, Assam - Sharma, Rashmita; Mina, Usha; Devi, Ashalata; Kumar, B. Mohan (Frontiers in Sustainable Food Systems, 2024)
Introduction Homegardens are one of the oldest agroforestry systems reported around the world. These agroforestry systems are often reported as harbingers of plant biodiversity conservation. However, a comprehensive understanding of these systems from the perspective of species level agrobiodiversity conservation is often missing. Methodology This study first visualizes the comprehensive role of homegardens in species level agrobiodiversity conservation and then assesses any variation in agrobiodiversity along diverse Socio-ecological Zones (SEZs) in the study site. The prominent SEZs identified in the study site were Protected Area (PA), Riverine (RI), Rural Market (RM), and Tea Estate (TE). Eight ethnic/linguistic groups were also identified at the study site. Agrobiodiversity inventorying of 192 homegardens from 16 villages was done. Results The results of the study highlight that homegardens in the study site have high species level agrobiodiversity concentration (101 total tree species reported, 39.58% of homegardens (HGs) had more than 10 varieties of vegetables, 68% had atleast one variety of bamboo, 76% had atleast one banana variety, 20.83% had pond). A total of 64% of HGs had livestock and around 85% had poultry. Moreover, this agrobiodiversity distribution also varied along different SEZs. The livestock diversity indices ranged from 0.49 (TE) to 1.04 (PA). The average plant diversity among homegarden was found to be in the range of 1.09 (PA) to 1.48 (TE) for Shannon, 0.45 (PA) to 0.66 (TE) for Simpson, 0.31 (PA) to 0.71 (TE) for Pileou evenness and 2.39 (PA) to 2.76 (RM) for Margalef. The plant composition reflected the dominance of the food species i.e. an average of 37% in each SEZ. Sorenson similarity index among different SEZs for plant and livestock was found to be highest between the HGs of the PA and RM (0.82). Among the ethnic/linguistic groups, the highest mean number of plant species (51) was found among the Mishing tribe. Also, high similarity index (0.78) was found in plant and livestock composition among the Mishing and the Bodo tribes. Discussion The findings imply that HGs exemplify diversified and integrated systems, showcasing their potential to play a crucial role in the development of sustainable food systems.